CSIG-34. LIN28B-LET-7-PBK PATHWAY IS AN IMPORTANT REGULATOR OF GROUP 3 MEDULLOBLASTOMA PROLIFERATION. (14th November 2022) - Shahab, Shubin; Sun, Jessica; Kunhiraman, Haritha; Schneiderjan, Matthew; Juraschka, Kyle; Kumar, Sachin; Taylor, Michael; MacDonald, Tobey; Kenney, Anna
Abstract: Children with Group 3 medulloblastoma (MB) have a very poor long-term outcome and many do not survive beyond 5 years. Several drivers for Group 3 MB have been identified but none have resulted in targeted therapy to date. LIN28B is a stem cell factor upregulated in Group 3 MB and is associated with worse survival. Here we investigate the role of the LIN28B pathway in Group 3 MB development. Pharmacologic inhibition of the LIN28B pathway is feasible and may provide a unique opportunity to target this tumor. Using LIN28B knockdown and overexpression in Group 3 MB cells we test LIN28B's effect on proliferation, self-renewal and metastasis. We investigate the effect of LIN28B knockdown on survival as well as proliferation and apoptosis markers using orthotopic xenografts in vivo. We also investigate the role of let-7 and its downstream target PBK on Group 3 MB proliferation. Finally, we use a LIN28 inhibitor 1632 and a PBK inhibitor HITOPK032 to treat Group 3 MB cell lines and then assess their impact on proliferation and apoptosis. We find that down-regulation of LIN28B or PBK using shRNA results in significant reduction in cell proliferation. In contrast overexpression of LIN28B increases Group 3 cell proliferation and tumor sphere formation. LIN28B knockdown also significantly (p< 0.01) increases survival in mice with orthotopic Group 3 tumors. The LIN28 inhibitor 1632 also leads to significant reduction in MB growth through decreased cell cycle entry and increased apoptosis. In addition, HITOPK032 also demonstrates significant reduction in Group 3 MB cell proliferation at low micromolar concentration. We also demonstrate that HITOPK032 in combination with CDK 4/6 inhibition can additively inhibit proliferation of Group 3 MB cells. Our study establishes a critical role for the LIN28B-let-7-PBK pathway in Group3 MB and provides encouraging preliminary preclinical results for drugs that target this pathway.